Farnesoid X Receptor Activation Attenuates Intestinal Ischemia Reperfusion Injury in Rats. - Laurens J Ceulemans; Len Verbeke; Jean-Paul Decuypere; Ricard Farré; Gert De Hertogh; Kaatje Lenaerts; Ina Jochmans; Diethard Monbaliu; Frederik Nevens; Jan Tack; Wim Laleman; Jacques Pirenne (PLoS ONE, 2017)
The farnesoid X receptor (FXR) is abundantly expressed in the ileum, where it exerts an enteroprotective role as a key regulator of intestinal innate immunity and homeostasis, as shown in pre-clinical models of inflammatory bowel disease. Since intestinal ischemia reperfusion injury (IRI) is characterized by hyperpermeability, bacterial translocation and inflammation, we aimed to investigate, for the first time, if the FXR-agonist obeticholic acid (OCA) could attenuate intestinal ischemia reperfusion injury.In a validated rat model of intestinal IRI (laparotomy + temporary mesenteric artery clamping), 3 conditions were tested (n = 16/group): laparotomy only (sham group); ischemia 60min+ reperfusion 60min + vehicle pretreatment (IR group); ischemia 60min + reperfusion 60min + OCA pretreatment (IR+OCA group). Vehicle or OCA (INT-747, 2*30mg/kg) was administered by gavage 24h and 4h prior to IRI. The following end-points were analyzed: 7-day survival; biomarkers of enterocyte viability (L-lactate, I-FABP); histology (morphologic injury to villi/crypts and villus length); intestinal permeability (Ussing chamber); endotoxin translocation (Lipopolysaccharide assay); cytokines (IL-6, IL-1-β, TNFα, IFN-γ IL-10, IL-13); apoptosis (cleaved caspase-3); and autophagy (LC3, p62).It was found that intestinal IRI was associated with high mortality (90%); loss of intestinal integrity (structurally and functionally); increased endotoxin translocation and pro-inflammatory cytokine production; and inhibition of autophagy. Conversely, OCA-pretreatment improved 7-day survival up to 50% which was associated with prevention of epithelial injury, preserved intestinal architecture and permeability. Additionally, FXR-agonism led to decreased pro-inflammatory cytokine release and alleviated autophagy inhibition.Pretreatment with OCA, an FXR-agonist, improves survival in a rodent model of intestinal IRI, preserves the gut barrier function and suppresses inflammation. These results turn FXR into a promising target for various conditions associated with intestinal ischemia.